Strangers in the night or love forever: Characteristics and preferences of short vs. long-term relationship seekers - Tadinac, Meri (Array, 2006)
Sex differences in mate preferences as well as in tendency to pursue long- vs. short-term relationships have often been explored and confirmed. Contrary to that, within sex analyses of who is more likely to engage in STR mostly remained of theoretical nature. Therefore, the aim of this study was to compare proportions of individuals interested in short-term relationship (if single) or extra-pair affair (if pair-bonded) in groups of different ages, incomes and education levels. While the proportion of single women interested in STR differed among those groups, men of all ages, incomes and education levels were equally interested in STR. The proportion of pair-bonded individuals interested in an extra-pair affair also differed among age groups (in both men and women) and income levels (in men only), but not across education levels. Furthermore, we tried to determine the structure of sex differences in mate preferences within temporal context of a relationship. Discriminat analyses showed that the mate preferences which mostly differentiated men from women seeking a short-term relationship were good looks and good financial prospect. Three more preferences differentiated men from women in a long-term relationship context: emotional stability and maturity, favorable social status and dependable character.